6x+1+(4x+8)x=5

Simple and best practice solution for 6x+1+(4x+8)x=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+1+(4x+8)x=5 equation:



6x+1+(4x+8)x=5
We move all terms to the left:
6x+1+(4x+8)x-(5)=0
We add all the numbers together, and all the variables
6x+(4x+8)x-4=0
We multiply parentheses
4x^2+6x+8x-4=0
We add all the numbers together, and all the variables
4x^2+14x-4=0
a = 4; b = 14; c = -4;
Δ = b2-4ac
Δ = 142-4·4·(-4)
Δ = 260
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{260}=\sqrt{4*65}=\sqrt{4}*\sqrt{65}=2\sqrt{65}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(14)-2\sqrt{65}}{2*4}=\frac{-14-2\sqrt{65}}{8} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(14)+2\sqrt{65}}{2*4}=\frac{-14+2\sqrt{65}}{8} $

See similar equations:

| (0.6x)-5=0.1x+7 | | -x+3-4x–8=30 | | –0.4(–x+1.6)=1.6 | | 2(10u-1)=-10-5(-4u+20) | | 109=-v+216 | | 8(q+1)=91 | | 4x+8+6x−5=33 | | –0.4(–x+1.6)=1.6 | | 5m-2=2m+4= | | −5(3x−11)=2(x−10)−27 | | -8b+5=21 | | 26=y/8 | | 2x^2+2=202 | | –0.4(x+1.6)=1.6 | | 5x−7=3x+1 | | 187=19-x | | 7a-13=8+4a | | y/1.5=4 | | 2/3(3/4x-1/6=1/2 | | 6(2j-7)=12j | | –0.4x+4=–1.6 | | 20+53.45x=58.45x | | 21=-3k | | x*61=4 | | 3y+-9=0 | | 20x+10x=420 | | -6(2r-11)=-12r | | x2-8x+16=36 | | 12(5x4.5)=36 | | 6/w=10/2 | | 19=y+11 | | 6n+15=-17n+19n-1 |

Equations solver categories